The impact of attitudes, motivational factors, and emotions on the image of a dark tourism site and the desire of the victims' descendants to visit it. Issue 3 (4th May 2022) - Abraham, Villy; Pizam, Abraham; Medeiros, Marcos
ABSTRACT: The present study explores the influence of attitudes, motivational factors, and emotions on the image of a Holocaust tourism site and ultimately, the desire of the victims' descendants to visit it. The study, which was conducted with an online questionnaire distributed to a purposeful sample of 243 second-generation Holocaust survivors residing in Israel, found that the image of this dark tourism site was a significant mediator between: (a) respondents' attitudes, (b) respondents' emotions of animosity and grief, (c) heritage motivations, and the intent to visit the destination in which the dark tourism site is located. The results also highlight the importance of respondents' feelings towards the country in which this dark tourism attraction is located. Respondents' health constraints emerged as a significant moderator in the relationship between the image of the dark tourism site and the desire to visit the country in which the attraction is located. The study concludes with implications and directions for future research.